Circulatory support devices: fundamental aspects and clinical management of bleeding and thrombosis. (25th September 2015) - Susen, S.; Rauch, A.; Van Belle, E.; Vincentelli, A.; Lenting, P. J.
Summary Circulatory support devices are increasingly being used to overcome cardiac or respiratory failure. Long‐term devices are used either as a 'bridge to transplant' to support patients who are unable to wait any longer for a heart transplant, or, more recently, as 'destination therapy' for older patients suffering from end‐stage heart failure and who have contraindications to heart transplantation. Short‐term support devices for high‐risk percutaneous coronary intervention, or as a 'bridge for decision' for patients suffering from refractory cardiogenic shock, have also been developed. The clinical benefit of such assist devices has been demonstrated in several important studies, but, unfortunately, thrombotic and bleeding complications are two major clinical issues in patients requiring these devices. Overcoming these issues is of major importance to allow the safe and broad use of these devices, and to consider them as true alternatives to heart transplantation. The present review focuses on thrombotic and bleeding complications, and describes how the risk of thrombosis and bleeding may vary according to the clinical indication, but also according to the type of device. We describe the current knowledge of the mechanisms underlying the occurrence of these complications, provide some guidance for choosing the most appropriate anticoagulation regimen to prevent their occurrence for each type of device and indication, and provide some recommendations for the management of patients when the complication occurs.